Direct Methanol Fuel Cells – Clean Energy Source for Future? - Patil Manesh B.; Sapkal V.S.; Sapkal R.S.; Bhagat S.L. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Fuel cells represent a clean alternative to current technologies for utilizing hydrocarbon fuel resources. Polymer electrolyte membrane fuel cells (PEMFCs) have acquired due importance as they are best suited for applications where a quick start up is required such as in automobiles. Direct methanol fuel cell (DMFC) is considered as a highly promising alternative power source. It is based on polymer electrolytes membrane (PEM) fuel cell technology. Direct methanol fuel cells are attractive for several applications, however, serious limitations still remain and need to be solved before developments of such devices and before they can become an alternative to internal combustion engines. It posses a number of advantages such as a liquid fuel, quick refueling, low cost of methanol and the compact cell design making it suitable for various potential applications including stationary and portable applications. DMFCs are also environmentally friendly. Although carbon dioxide is produced, there is no production of sulfur or nitrogen oxides. The development of commercial DMFCs has nevertheless been hindered by some important issues. The most important are the low power density caused by the slow electrochemical methanol oxidation at the anode and methanol crossover through PEM, which is responsible for inhibiting the activity of the cathode catalyst as well. At present, methanol crossover from the anode to the cathode appears to be the major limitation. This article reviews the development of direct methanol fuel cells, technical challenges and current status.